Effects of Biogas Residues on Dissipation of Difenoconazole in Paddy Sediment System Under Field Conditions - Yu, Lina; Wen, Yong; Luo, Xuhui; Xiang, Yun; Yuan, Xufeng; Pang, Sen; Ma, Xiaodong; Li, Xuefeng (Frontiers in Environmental Science, 2022)
Little is known about whether the application of biogas residues in rice fields will affect the degradation of pesticides. This study investigated the dissipation behavior of the fungicide difenoconazole in paddy water and sediment after the application of a chemical fertilizer or biogas residues. The results showed that the application of biogas residues changes the dissipation of difenoconazole in both paddy water and sediment. The half-lives of difenoconazole in paddy water and sediment with biogas residues were 0.50 and 10.09 days, respectively, while the half-lives of difenoconazole in paddy water and sediment with chemical fertilizer were only 0.22 and 4.64 days, respectively. After biogas residues were applied in a paddy field, no significant changes in pH value of paddy water and sediment and soil microorganisms were observed, but soil organic matter decreased by 30%. The above studies suggest that biogas residues may affect the dissipation of pesticides in paddy field water and sediments, which provides a new focus on the scientific and rational use of biogas residues as organic fertilizer in rice fields.